White Supervisor and Subordinate Beliefs about Black/White Inequality: Implications for Understanding and Reducing Workplace Racial Disparities. (1st May 2020) - Smith, Ryan A; Hunt, Matthew O
Abstract: This study examines the racial stratification beliefs of white Americans who have decision-making power at work (managers and supervisors) and of those (subordinates) who lack such power. We focus on whether these groups vary in overall levels of support for, and in determinants of, beliefs about racial inequality. Pooled cross-sectional analyses of data from the 1977 to 2014 General Social Surveys (GSS) reveal that, among both white supervisors and subordinates, support is greatest for a motivation-based explanation of black disadvantage, followed by (in order) explanations focusing on blacks' lesser educational chances, discrimination against blacks, and finally, blacks' supposed lesser ability. In line with Group Position Theory, our multivariate analyses reveal few differences across the supervisory divide in levels of support for, or in the determinants of, whites' beliefs about black disadvantage. Differences that do exist align with alternative perspectives including Social Dominance Theory, a Group Self-Interest Model, and Intergroup Contact Theory. We conclude by discussing the theoretical and methodological implications of our findings for future research pertaining to what does and does not work to ameliorate racial inequality in the workplace.